Dynamic profile of the microbiota during coconut water pre-fermentation for nata de coco production. (August 2017) - Zhang, Jiachao; Yang, Yichong; Deng, Jian; Wang, Yanmei; Hu, Qisong; Li, Congfa; Liu, Sixin
Abstract: The uncontrolled coconut water pre-fermentation process represents a considerable food safety risk and can cause unstable production. In the present study, a metagenomics approach was used to explore the dynamic changes in the microbial structure and their correlation with the physicochemical indices of coconut water during pre-fermentation. At the generic level, Leuconostoc, Lactobacillus, Acetobacter and Weissella were the predominant bacteria during pre-fermentation. Using the RDP database, we detected 28 and 34 core OTUs in samples from the cities of Wenchang and Haikou (Hainan province, China) that primarily belonged to the genera Leuconostoc and Lactobacillus . The PCoA, based on Weighted Unifrac distances, demonstrated that the microbial community structure changed significantly during pre-fermentation, and these structural changes could be attributed to an increase in bacteria of the genera Lactobacillus and Acetobacter . Additionally, we observed that the pH values decreased significantly, whereas the lactic acid and acetic acid content increased during pre-fermentation. A significant positive correlation was observed between the OTUs representing Lactobacillus and Acetobacter and the lactic acid content. This study is intended as a theoretical guide for controlling and accelerating pre-fermentation, inhibiting or eliminating harmful contaminating microorganisms, especially pathogens and, finally, raising the yield of nata de coco for further research. Highlights: Leuconostoc, Lactobacillus and Weissella were predominant genus during pre-fermentation. The structure change can be attributed to the increased genera of Lactobacillus and Acetobacter. A significant positive correlation was observed between Lactobacillus and organic acid. This research will provide theoretical guide for controlling and speeding the pre-fermentation.